Mixed-valence gold-porphyrin two-dimensional coordination networks for repurposing of chrysotherapy - Zhou, Gaoxin (2024)
Catalytic gold nanomaterials typically exhibit antibacterial properties, albeit significantly weaker than ionic gold in chrysotherapy. The inherent stability of gold nanoparticles prevents the release of gold ions, limiting their ability to achieve efficient antibacterial therapy. To address this limitation, we propose a novel sustained ionic gold release strategy through the construction of a mixed-valence gold-porphyrin coordination network (Au-Por). By adjusting the ratio of Au to porphyrin molecule, an ultrathin two-dimensional Au-Por nanosheet was successfully synthesized, which contains 85.9 % of Au (III). In addition, the remaining gold existed in the form of uniformly distributed ultrasmall nanoclusters on the Au-Por nanosheet. Notably, the Au-Por nanosheet exhibited a sustained release of gold ions. Thus, a multimodal antibacterial therapy was achieved by integrating the direct bactericidal action of ionic gold and lethal reactive oxygen species (ROS) generated through the peroxidase (POD)-like activity of gold nanoclusters and photodynamic therapy (PDT) using porphyrins. The innovative Au-Por exerted broad-spectrum bactericidal activity against both Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus bacteria mediated by bacterial membrane disruption and DNA damage. Moreover, in vivo studies demonstrated the synergistic effect of Au-Por on combating skin wound infections and facilitating wound healing. Comprehensive safety evaluations proved that Au-Por exhibited no hematotoxicity or hepatorenal toxicity, and it also displayed rapid renal clearance after treatment, indicating favorable biocompatibility. The repurposing of chrysotherapy has revolutionized the antibacterial strategy of nanoscale gold, resulting in a dramatic boost in antibacterial activity and valuable insights for designing highly efficient nanoscale antibacterial agents.